Management of Funds Not to Be Recognized as Income (TBDSP) in Islamic Financial Institutions, Businesses, and the Economy Based on Fatwa DSN-MUI - Maulani Salsabila; Jajang Saepul Hamzah (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2025)
The operational practices of Islamic Financial Institutions, Islamic Business Institutions, and Islamic Economic Institutions in Indonesia still face challenges due to the dominance of conventional systems, regulatory limitations, and the low level of public understanding of sharia principles. This situation is often unavoidable, which can potentially lead to funds that should not be recognized as income (TBDSP). Therefore, managing TBDSP funds becomes an important issue in maintaining the integrity and trust in the Islamic institution system. This study aims to analyze the provisions and mechanisms for managing TBDSP based on DSN-MUI Fatwa No.123/DSN-MUI/XI/2018. The method used is a literature review by examining the DSN-MUI, related regulations, and relevant academic literature regarding the management of non-halal funds in Islamic institutions. The analysis is conducted descriptively-qualitatively to describe the management, including the urgency of regulation, objectives, and limitations of TBDSP within the framework of Islamic economic law. The results show that TBDSP can originate from usury (riba), defective contracts, late penalties, and funds with unclear ownership. Its management must be separated into a special account and channeled for social interests and the welfare of the community. This fatwa DSN-MUI emphasizes the prohibition of using TBDSP for internal institutional purposes, such as promotion or employee training. Thus, fatwa DSN-MUI No.123/2018 plays an important role in strengthening transparency, accountability, and consistency in Islamic financial practices in Indonesia.